2018
DOI: 10.5545/sv-jme.2018.5238
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Pressures Influenced by Trapped Air Pockets in Water-Filled Pipelines

Abstract: mm). A trapped air pocket is confined at the downstream end of the pipeline. The transient event is initiated by rapid opening of a valve positioned at the initial air/water interface. The shut-down test case has been carried out in the University of Adelaide laboratory apparatus (length 37 m, internal diameter 22 mm). A trapped gas pocket is maintained near the midpoint of the pipeline. The shut-down event is initiated by rapid closure of the downstream-end valve. Results of numerical simulations and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The associated transient responses and failure mechanisms tend to be complex and difficult to predict. Previous studies (Zhou et al 2002a;Wright et al 2011;Bergant et al 2018) indicated that large pressure surges induced by air entrapment and release (air expulsion) often play a crucial role in how these events unfold.…”
Section: Introductionmentioning
confidence: 99%
“…The associated transient responses and failure mechanisms tend to be complex and difficult to predict. Previous studies (Zhou et al 2002a;Wright et al 2011;Bergant et al 2018) indicated that large pressure surges induced by air entrapment and release (air expulsion) often play a crucial role in how these events unfold.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattarai et al (2019) noted that optimization of the air chamber design process has largely focused on numerical analyses. As a result, limited experimental investigations have involved high-frequency transient testing of small off-line pockets using valve movement times in the order of 1-10 ms. Kim (2008b) and Bergant et al (2018) carried out high-frequency transient testing for the case where the off-line cavity is entirely filled with air and there is no separating water column between the main pipe and the air-water interface. The off-line pocket was found to reduce the local wave speed and created out-of-phase reflections.…”
Section: Introductionmentioning
confidence: 99%
“…the branch junction can be treated and observed as a membraneshell. In case of appearance of the trapped air pockets, pressure will become unsteady [13] and [14]. This paper analysis only steady pressure.…”
Section: Resultsmentioning
confidence: 99%